CERITA RAKYAT “BELU MAU, SABU MAU, DAN TI’I MAU” SEBAGAI IKATAN TIGA SUKU BANGSA DAN NILAI KEARIFAN LOKAL - Erwin Syahputra Kembaren; Salimulloh Tegar Sanubarianto (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2021)
Geographically, Belu, Sabu, and Rote (Ti'i) are three regencies located on three islandsfar apart in the province of East Nusa Tenggara. The three islands, regencies, and ethnic groups share folk tales that have become legends and rarely known by society and even researched. The purpose of this research is to reveal the local wisdom values contained in the folk tales of